Plasma Kallikrein as a Modulator of Liver Injury/Remodeling - Ibrahim A Ahmed; Miran A Jaffa; Mayssam Moussa; Duaa Hatem; Duaa Hatem; Ghewa A El-Achkar; Rola Al Sayegh; Rola Al Sayegh; Mia Karam; Mia Karam; Eva Hamade; Aida Habib; et al. (Frontiers Media S.A., 2021)
The occurrence and persistence of hepatic injury which arises from cell death and inflammation result in liver disease. The processes that lead to liver injury progression and resolution are still not fully delineated. The plasma kallikrein-kinin system (PKKS) has been shown to play diverse functions in coagulation, tissue injury, and inflammation, but its role in liver injury has not been defined yet. In this study, we have characterized the role of the PKKS at various stages of liver injury in mice, as well as the direct effects of plasma kallikrein on human hepatocellular carcinoma cell line (HepG2). Histological, immunohistochemical, and gene expression analyses were utilized to assess cell injury on inflammatory and fibrotic factors. Acute liver injury triggered by carbon tetrachloride (CCl4) injection resulted in significant upregulation of the plasma kallikrein gene (Klkb1) and was highly associated with the high mobility group box 1 gene, the marker of cell death (r = 0.75, p < 0.0005, n = 7). In addition, increased protein expression of plasma kallikrein was observed as clusters around necrotic areas. Plasma kallikrein treatment significantly increased the proliferation of CCl4-induced HepG2 cells and induced a significant increase in the gene expression of the thrombin receptor (protease activated receptor-1), interleukin 1 beta, and lectin-galactose binding soluble 3 (galectin-3) (p < 0.05, n = 4). Temporal variations in the stages of liver fibrosis were associated with an increase in the mRNA levels of bradykinin receptors: beta 1 and 2 genes (p < 0.05; n = 3-10). In conclusion, these findings indicate that plasma kallikrein may play diverse roles in liver injury, inflammation, and fibrosis, and suggest that plasma kallikrein may be a target for intervention in the states of liver injury.